Níveis de cama de aviário e nitrogênio em cobertura na cultura do milho - Rezzadori, Cleiton (2016)
Corn (Zea mays) stands out in the Brazilian agricultural scenario to be the most produced cereal, and in this context, nitrogen plays an important role on crop development and have been shown significant effect on increasing yield. Poultry litter used as organic fertilizer for the corn crop is the best use of this residue, but when overused by farmers, this organic compound may exceed the levels of potassium and phosphorus needed and cause environmental damage. This study aimed to evaluate the efficiency of poultry litter rates in combination with nitrogen applied in sidedress on corn yield potential and a possible residual effect of this fertilization on black oat (Avena strigosa) dry matter yield cultivated as the next crop. Experiment was carried out at the Federal Technological University of Paraná (UTFPR) Campus of Dois Vizinhos, from September, 2014 up to July 2015 in a randomized block design with three replications divided into two experimental protocols. At the first protocol, treatments consisted of 0, 6, 12 and 18 t ha-1 of poultry litter and at 2nd the use of 6 t ha-1 of poultry litter combined with 0, 75, 150 and 225 kg ha-1 of nitrogen applied in sidedress on corn. Both protocols were compared with control treatment consisting of mineral fertilizer recommended to the corn crop using 45 kg ha-1 N, 120 kg P2O5 ha-1 and 120 kg ha-1 of K2O applied at the sowing line and 150 kg ha-1 of N applied in sidedress. It was evaluated: corn plant population, number of rows per ear, number of kernels per row, number of grains per ear, thousand grain weight and grain yield. Regarding to the black oat, dry matter production was evaluated. Among poultry litter levels, the use of 18 t ha-1 showed the highest yield, with 13,659 kg ha-1, and corn yield at the treatment with 12 t ha-1 or more showed higher corn yield than the treatment with mineral fertilizer. At the treatment mixing poultry litter with nitrogen rates, the use of 225 kg ha-1 N showed the highest yield with 10,864 kg ha-1, while to the treatment with mineral fertilizer, yield was similar to the treatment without nitrogen in sidedress with 9,509 kg ha-1. Regarding black oat dry matter yield, the treatment with 18 t ha-1 of poultry litter showed the highest yield, with 5,763 kg ha-1. And with the use of nitrogen in sidedress, the use of only 6 t ha-1 of poultry litter provided the highest dry matter yield with 4,793 kg ha-1. The use of organic fertilizer in appropriate levels provides greater corn yield, as well as its use remains in a residual manner in the soil for the successor culture providing higher yields.